KEBEBASAN DAN PENEBUSAN SEBAGAI WUJUD KESEMPURNAAN KASIH ALLAH: SUATU TELAAH TEOLOGI PENTAKOSTAL ATAS RELASI ALLAH DAN MANUSIA - Sitorus, Reynhart Yegar; Santosa, Nur Budi (The Way: Jurnal Teologi dan Kependidikan, 2026)
The relationship between God and humanity is a central theme in Christian theology, often discussed through various theological approaches. In this regard, the factor of redemption often receives greater attention than human freedom, even though both are closely related in understanding God's love as a whole. This article aims to examine freedom and redemption as a theological unity that expresses the perfection of God's love from a Pentecostal theological perspective. This research uses a qualitative method with a literature study approach to biblical texts and relevant Pentecostal theological literature. The results of the study indicate that freedom is given by God as a relational space so that humans can respond to His love consciously and responsibly. However, this freedom also opens up the possibility of sin and relational separation. In this context, redemption is understood as an initiative of God's love that does not eliminate human freedom, but rather restores broken relationships through the work of Christ. This restoration of relationships opens up space for the presence and work of the Holy Spirit for every believer, which is especially the basis of the faith and spirituality of Pentecostals. Therefore, freedom and redemption together reveal the perfection of God's love, as a love that creates living relationships, restores failures, and remains actively present in His relationship with humanity.